Geotourism Contribution To Sustainable Develeopment In Ranah Minang Silokek Geopark Sijunjung District - Ade Irwandi; Indah Sari Rahmaini; Edi Indrizal; Ermayanti Ermayanti; Benny Dwifa Yuswir; Zefnihan Zefnihan (Badan Pelaksana Rinjani-geopark Rinjani Lombok, 2024)
This paper aims to explain the contribution of tourism development developed in the geoparks area with the concept of geotourism. The Ranah Minang Silokek geopark area in Sijunjung Regency is attractive and has developed destinations in the form of geodiversity, biodiversity, and cultural diversity. Although tourism can generally produce a sustainable life, cultural and heritage tourism can have a positive or negative impact on people's lives significantly. Thus, the extent of the contribution of sustainable tourism development through tourism in Silokek Geoparks. Through qualitative methods and a narrative approach, it can be seen the objects in Silokek developed as geotourism based on sustainable tourism development. This shows that the development of geotourism can give a good impact, not only supporting economic growth (community and government) but as a basis for efforts to preserve and protect natural and geological landscapes as the main headline of the Silokek geoparks. So that the perspective changes that geotourism is the antithesis of mass tourism that has contributed to the principles of geoparks (Unesco Global Geoparks Network).